2020
DOI: 10.1002/suco.201900534
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of shear‐flexural behavior of precast joints in prestressed reinforced concrete

Abstract: The behavior of precast concrete structures at the limit states of ultimate bearing capacity depends on the shear and shear-flexural behavior of the joints between precast components, such as shear wall and beam-column joints, or between the precast component and footing. This study presented a series of tests on the shear-flexural behavior of precast concrete joints applied in precast structures with high strength reinforcement. The tested parameters of the specimens included the joint type, shear-span ratio,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…From the visual inspection of this building, many cracks, gaps and holes at wall's connection can be clearly observed due to poor grout materials and low quality of construction, as presented in Figure 1. These deterioration and defects at reinforced concrete (RC) wall's joints may cause insufficient ductility of both precast and cast in‐situ wall systems during extreme wind load, leading to brittle failure 3–5 . These have ignited concerns to identify the building's dynamic performances under current environmental circumstance like wind load so engineers can provide timely maintenance services while ensuring the safety of residents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the visual inspection of this building, many cracks, gaps and holes at wall's connection can be clearly observed due to poor grout materials and low quality of construction, as presented in Figure 1. These deterioration and defects at reinforced concrete (RC) wall's joints may cause insufficient ductility of both precast and cast in‐situ wall systems during extreme wind load, leading to brittle failure 3–5 . These have ignited concerns to identify the building's dynamic performances under current environmental circumstance like wind load so engineers can provide timely maintenance services while ensuring the safety of residents.…”
Section: Introductionmentioning
confidence: 99%
“…These deterioration and defects at reinforced concrete (RC) wall's joints may cause insufficient ductility of both precast and cast in-situ wall systems during extreme wind load, leading to brittle failure. [3][4][5] These have ignited concerns to identify the building's dynamic performances under current environmental circumstance like wind load so engineers can provide timely maintenance services while ensuring the safety of residents.…”
Section: Introductionmentioning
confidence: 99%
“…The test results demonstrated that the prestressed precast connection contained a higher collapse-resisting capability, and the tensile catenary effects in prestressed specimen were improved to some extent. Zhi et al [21] experimentally investigated the shear-flexural performance of prestressed precast joints with high strength reinforcement, and the parameters of joint type, span ratio, initial prestress and longitudinal ratio were analyzed. The results indicated that the crack behaviors and shear capacities can be well enhanced with the control of prestress, and the equivalent performance to the monolithic specimen can be satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the seismic performance of the PC structural system is mainly affected by the behavior of the connections between the PC members as well as between the PC members and the foundation. In the current literature, extensive investigations on seismic performance and jointed connection technology related to PC structural systems have been systematically reported, 4–7 some of which reveal that the structural systems adopting the PC shear walls as the main lateral and vertical force resistance provide good seismic behavior.…”
Section: Introductionmentioning
confidence: 99%